Introductory foods - Bennion, Marion, 1925-; Scheule, Barbara (Upper Saddle River, N.J. : Prentice Hall, 2000)
This book provides knowledge about the basic fundamental principles of food preparation and to alert them to many innovations in science and technology related to foods.
Keywords: Food; Cookery; Cookery; Food